In Vitro Bioactivities of Food Grade Extracts from Yarrow (Achillea millefolium L) and Stinging Nettle (Urtica dioica L) Leaves - Mannila Enni; Marti-Quijal Francisco J; Selma-Royo Marta; Calatayud Marta; Falcó Irene; de la Fuente Beatriz; Barba Francisco J; Collado Maria Carmen; Linderborg Kaisa M (Springer, 2022)
Yarrow (Achillea millefolium L., AM) and nettle (Urtica dioica L., UD) are bioactive plants used commercially in functional food and supplement applications and traditionally to alleviate gastric disorders. In this work, the effects of food-grade optimized extracts of Finnish early-season AM and UD were tested on bacterial growth including potential beneficial and foodborne pathogens, as well as murine norovirus (MNV). The anti-inflammatory properties of the extracts were also tested in vitro by NF-κB reporter cells. The food-grade extraction was optimized with the response surface modelling in terms of total carotenoid, chlorophyll, and phenolic compounds contents and antioxidant capacities. The optimal food-grade extraction parameters were a 1-h extraction in 70% ethanol at 45 °C for AM, and at 49 °C for UD. There were no significant effects on the beneficial bacteria (Lacticaseibacillus and Bifidobacterium strains), and the extracts were more effective against gram-positive than gram-negative foodborne bacteria and potential pathogens. Listeria innocua was the most susceptible strain in the optimized extracts with a growth rate of 0.059 ± 0.004 for AM and 0.067 ± 0.006 for UD, p < 0.05 compared to control. The optimized extracts showed a logarithmic growth reduction of 0.67 compared to MNV. The hydroethanolic extracts were cytotoxic to both cell lines, whereas aqueous AM and UD extracts induced and reduced TLR4 signalling in a reporter cell line, respectively. The results provide novel food-grade extraction parameters and support the bioactive effects of AM and UD in functional food applications, but more research is needed to elucidate the precise biological activity in vivo for gastric health.